THE IMPACT OF COUPLED SUPPORT ON VEGETABLES GROWN IN GREENHOUSES AND PLASTIC TUNNELS IN ROMANIA - Cornelia ALBOIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents the impact of the coupled support on vegetables cultivated in green houses and plastic tunnels in Romania. In this study, a etailed analysis is carried out on the coupled support received by farmers for vegetables grown in greenhouses and plastic tunnels in the eriod 2015-2018. The main indicators used refer to the evolution of cultivated areas, both in field and in greenhouses and plastic tunnels, he evolution of productions and yields, and trade balance. The paper also presents an analysis of the evolution of the number of farmers who eceived coupled support, of the areas entitled to payment and of the coupled support calculated per hectare in territorial profile. The nalysis is based on data provided by the Agency for Payments and Intervention in Agriculture and the National Institute of Statistics. The esults reveal a low impact of the coupled support on the main analyzed indicators, as well as the lack of consistency in the support provided n the investigated period.